2019
DOI: 10.3390/ma12203325
|View full text |Cite
|
Sign up to set email alerts
|

Biological Assessment of Zn–Based Absorbable Metals for Ureteral Stent Applications

Abstract: The use of ureteral stents to relieve urinary tract obstruction is still challenged by the problems of infection, encrustation, and compression, leading to the need for early removal procedures. Biodegradable ureteral stents, commonly made of polymers, have been proposed to overcome these problems. Recently, absorbable metals have been considered as potential materials offering both biodegradation and strength. This work proposed zinc-based absorbable metals by firstly evaluating their cytocompatibility toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 61 publications
3
9
0
Order By: Relevance
“…In this work, it was presented that the amount of Zn 2+ ions below 100.8 μM (11.4 mg/L) in pure Zn, 98.2 μM (11.1 mg/L) in the Zn‐3Ag alloy, and 118.5 μM (13.4 mg/L) in the Zn‐3Ag‐0.5Mg provide a favorable environment for cell survival and proliferation. This result is consistent with other already mentioned results for Zn‐based materials 45,62,68–71 . Furthermore, it can be seen that in the current study, the chemical composition variations of the investigated samples revealed almost no significant differences.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this work, it was presented that the amount of Zn 2+ ions below 100.8 μM (11.4 mg/L) in pure Zn, 98.2 μM (11.1 mg/L) in the Zn‐3Ag alloy, and 118.5 μM (13.4 mg/L) in the Zn‐3Ag‐0.5Mg provide a favorable environment for cell survival and proliferation. This result is consistent with other already mentioned results for Zn‐based materials 45,62,68–71 . Furthermore, it can be seen that in the current study, the chemical composition variations of the investigated samples revealed almost no significant differences.…”
Section: Discussionsupporting
confidence: 93%
“…It has also been reported that at low concentrations, Zn had no adverse effects on endothelial cell viability, while the amount of Zn 2+ over 100 μM significantly decreased cell viability, and above 80 μM inhibited cell proliferation 67 . In general, high Zn 2+ concentrations contribute to cell death, however, at a much lower Zn 2+ ion concentration, Zn can even be beneficial for cell proliferation 45,62,68–70 . In this work, it was presented that the amount of Zn 2+ ions below 100.8 μM (11.4 mg/L) in pure Zn, 98.2 μM (11.1 mg/L) in the Zn‐3Ag alloy, and 118.5 μM (13.4 mg/L) in the Zn‐3Ag‐0.5Mg provide a favorable environment for cell survival and proliferation.…”
Section: Discussionmentioning
confidence: 70%
“…Obviously, "crystal-like" degradation products were observed at high magnification (Figure 4b,e), in line with previous studies [19,37]. Moreover, EDX analysis (Figure 4c,f) showed that these degradation products were mainly composed of Zn, P, O, and C, indicating that these degradation layers might be phosphates and carbonates, as previously reported [38][39][40]. magnification (Figure 4b,e), in line with previous studies [19,37].…”
Section: In Vitro Degradation Behaviorsupporting
confidence: 91%
“…Furthermore, electron microscopy indicated the maturation of uroplakin plaques and the presence of discoid and fusiform vesicles near the plasma membranes, and immunostaining of uroplakins, tight junction proteins, and various markers such as keratins. These reconstructed tissues were used as models to study several pathologies such as bladder cancer[ 196 ], ketamine-induced cystitis[ 197 ] or the effect of metallic stent use[ 198 ]. Soon after, the preservation of epithelial SCs ( i.e.…”
Section: The Self-assembly Approach For Genitourinary Tissue Engineeringmentioning
confidence: 99%